Two-Stage Scheme for Disturbance Rejection Hovering Control of Underwater Vehicles - Bi, Anyuan; Feng, Zhengping; Zhu, Yuchen; Deng, Xu (Shanghai jiao tong da xue xue bao, 2022)
A two-stage model-independent hovering control scheme for underwater vehicles, which are subject to unknown yet constant external disturbance, to eliminate steady-state depth error is proposed. Proportional-derivative (PD) state feedback control law is adopted as the ballast mass planner at the first stage for the vehicle to reach both hydrostatic balance and a steady depth. The residual depth error is then removed by an additional disturbance rejection control at the second stage. Global asymptotic stability of the whole system is guaranteed via Lyapunov approach. The effectiveness of the proposed scheme is illustrated by the simulation of diving control of an underwater vehicle with hydraulic variable ballast system.